2014
DOI: 10.4028/www.scientific.net/amm.590.805
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Parameter Estimation Method for Drug Diffusion, Distribution and Clearance in the Rat Brain Extracellular Space

Abstract: Purposes to estimate parameters for gadolium-diethylenetriaminepentaacetic acid (Gd-DTPA) diffusion and distribution after drug delivery in the rat brain extracellular space (ECS). Methods An isotropic diffusion pattern in the homogeneous media was presumed for Gd-DTPA diffusion in the rat brain ECS, and a mathematical model was established to describe the pharmacokinetics of Gd-DTPA. Results the analytical solution of the diffusion equation was obtained by Laplace transform, and the least square method was ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this study, the diffusion coefficients calculated along the three orthogonal axes were approximate to the coefficient (0.0129 mm 2 /h) of drugs isotropic diffusion in a homogeneous medium . The diffusion coefficient along the rostrocaudal direction was larger than the coefficient along the x ‐axes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, the diffusion coefficients calculated along the three orthogonal axes were approximate to the coefficient (0.0129 mm 2 /h) of drugs isotropic diffusion in a homogeneous medium . The diffusion coefficient along the rostrocaudal direction was larger than the coefficient along the x ‐axes.…”
Section: Discussionmentioning
confidence: 85%
“…The diffusion coefficients of Gd‐DTPA molecules acquired in the rat brain were much lower than its diffusion coefficient (3.816 mm 2 /h) in the gel phantom (0.3% (w/v), 37°C), which demonstrated that the movements of Gd‐DTPA molecules were hindered severely. This is related to the characteristics of ECS in the rat brain.…”
Section: Discussionmentioning
confidence: 91%